The Principle of Shura and the Role of the Umma in Islam - Fazlur Rahman (International Institute of Islamic Thought, 1984)
Muslims, or at least the vast majority of them, have been very vocal about the necessity of establishingan Islamic state in the world, or, if it is not possible, to set up a unitary Islamic state, at least, several Islamic states. The idea of an Islamic state has many implications touching both the form and the substance of the state and raising questions like unity and multiplicity of such states, the nature of legislation and source of power and whether or not it ought to be a democracy. In this paper, I shall discuss only this last question which immediately concerns only the form of the state but which has obvious far-reaching consequences for substantive issues as well-for example, the source of power and the nature of legislation. But, although Muslims have been very anxiously expressing the need for an Islamic state, there is little consensus on any of the basic matters mentioned above, the least on the issue to be discussed in this paper, viz., the form of an Islamic state. Yet, the absolutely fundamental importance of the issue cannot be denied since it centrally involves the question of the Muslim Umma and the nature of its role in an Islamic state. We will first try to delineate the bearing that the teaching of the Qur’an has on the subject, then briefly characterize both the views of the classical Muslim jurists and the practice of the historic community. Then, we will give the essentials of the current positions and, finally, indicate our conclusion. The Qur’an formally announced the establishment of the Muslim community in Madina in connection with three events: the declaration of the incumbency of the Hajiof the Ka’ba upon Muslims, the declaration of the duty of Jihad and the change of the Qibla from Jerusalem to the Ka‘ba. We will not go here into the question of the timing of these events because it has no direct bearing on our present problem. It is sutficient to point out that the pilgrimage was the first to be announced, then probably came Jihad and then the change in the Qibla. Be that as it may, the Haji and Jihad are treated in close approximity to each other in Sura 22 (al-Haji), while the Haji and the Qibla change appear close to each other in Sura 2 (al-Baqara), the two Suras being contemporary or closely ...